Long term follow-up of a family with GUCY2D dominant cone dystrophy - Tsokolas, Georgios (Int J Ophthalmol, 2018)
AIM: To describe long term follow-up in a family with GUCY2D dominant cone dystrophy. METHODS: Optical coherence tomography scans and fundus autofluorescence images were obtained. Flash and pattern electroretinograms (ERGs) and occipital pattern reversal visual evoked potentials were recorded. RESULTS: Two members of the same family (father and son) were identified to have the heterozygous R838C mutation in the GUCY2D gene. The father presented at the age of 45 with bilateral bull's eye maculopathy and temporal disc pallor. Over 13y of serial follow up visits, the bull's eye maculopathy progressed gradually into macular atrophy. Electrophysiological tests were significantly degraded suggesting poor macular function. Spectral-domain optical coherence tomography (SD-OCT) scans showed progressive loss and disruption of the ellipsoid layer at the foveal level. His son presented at the age of 16 with bilateral granular retinal pigment epithelial changes in both maculae. Electrophysiological testing was initially borderline normal but has gradually deteriorated to show reduced cone ERGs and macula function. SD-OCT demonstrated gradual macular thinning and atrophy bilaterally. Unlike his father, there was no disruption of the ellipsoid layer. CONCLUSION: Both family members exhibited gradual changes in their fundi, electrophysiological testing and multimodal imaging. Changes were milder than those observed in other mutations of the same gene.